In Vitro Anti-Inflammatory Activities of Ethanolic Extract Elephantopus Scaber Leaves - Tomy Nurtamin; I Putu Sudayasa; Tien Tien (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Inflammation is a protective physiological response to tissue injury that can be caused by harmful stimuli. If the inflammatory process is prolonged and cannot restore to homeostatic conditions, this may lead to pathological effects that can damage cells and cause various diseases. Elephantopus scaber is a plant that can easily be found in Indonesia. Elephantopus scaber is a type of plant that is often used as a traditional medicines. Several studies have shown that the compound bioactive content contained in plants has enormous potential as alternative medicine.Objective: This present study was to investigate the anti-inflammatory activity of ethanolic extract of Elephantopus scabe leaves.Methods: The Elephantopus scaber leaves were extracted using ethanol solvent into different concentration (50 mg/mL, 100 mg/mL, and 120 mg/mL). Diclofenac sodium was used as the standard. Anti-inflammatory assays were performed by the human red blood cell (HRBC) membrane stabilization method and heat-induced hemolysis method. Phytochemical screening that used in the present study was a conventional method.Results: Phytochemical screening showed the presence of flavonoids, tannins, and saponins. In the present study, ethanolic extract of Elephantopus scaber leaves has anti inflammatory activity by protecting the stability of red blood cell membrane. The highest protection capability possessed by the ethanolic extract of Elephantopus scaber leaves in both human red blood cell (HRBC) membrane stabilization method and heatinduced hemolysis method was at a concentration of 100 mg/mL.Conclusion: The ethanolic extract of Elephantophus scaber has antiinflammatory activities by in vitro assays.